1988
DOI: 10.1111/j.1365-2125.1988.tb05277.x
|View full text |Cite
|
Sign up to set email alerts
|

The calcium‐channel blocker, verapamil, does not improve portal pressure in patients with alcoholic cirrhosis.

Abstract: 1. Recently the calcium‐channel blocker, verapamil, has been reported to decrease portal pressure in rats with experimental cirrhosis and in patients with liver cirrhosis. 2. In eight patients with alcoholic cirrhosis the effect of verapamil (5 mg i.v.) on systemic and splanchnic haemodynamics was investigated. 3. Mean arterial pressure, wedged hepatic venous pressure, hepatic venous pressure gradient, and verapamil plasma concentrations were measured before and at 10, 20, 30 min following 5 mg i.v. administra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1990
1990
1999
1999

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Thus, Miotti & Reichen (1985) found a decrease in the elimination rate constant of ICG after verapamil. However, the use of the elimination rate constant of ICG as an estimate of liver function may lead to errors due to variations in volume of distribution or in liver blood flow (Keiding, 1987), as might occur after verapamil administration (Lay et al, 1988;Merkel et al, 1988). Kong et al (1986) observed an increase in serum albumin levels after 3 months of verapamil administration.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, Miotti & Reichen (1985) found a decrease in the elimination rate constant of ICG after verapamil. However, the use of the elimination rate constant of ICG as an estimate of liver function may lead to errors due to variations in volume of distribution or in liver blood flow (Keiding, 1987), as might occur after verapamil administration (Lay et al, 1988;Merkel et al, 1988). Kong et al (1986) observed an increase in serum albumin levels after 3 months of verapamil administration.…”
Section: Discussionmentioning
confidence: 99%